The role of human capital investments in business excellence of Croatian companies - Tadić, Ivana (Economic and business review, 2022)
The paper analyses human capital investments and their relation to company performance in Croatia. Human capital represents an inevitable element in recognising and measuring an organisation's values and supporting its business excellence. The results obtained show that training and extra bonuses or salaries are positively correlated with company excellence, as well as show a significant difference in the mean of salaries per employee between high and moderate intensive intellectual capital companies. The differences in company excellence, when human capital expenditures are capitalized in a company's balance sheet rather than recognized as expenses in the company's profit and loss account, is confirmed. Companies should pay attention to managing human resources and realizing their importance for business excellence, as well as the importance of appropriate recognition and measurement of human capital in financial statements.
Keywords: company performance; človeški kapital; human capital; management; poslovanje podjetja